2021
DOI: 10.1016/j.cpcardiol.2020.100744
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Coronary Artery Thrombosis: A New Challenging Finding in COVID-19 Patients and ST-elevation Myocardial Infarction

Abstract: As the COVID-19 pandemic continues, more information on the non-respiratory effects of the coronavirus is obtained. Cardiovascular complications, especially acute coronary syndromes, are rare. However, they prove to be effective factors in the mortality rate of COVID-19 subjects. Acute ST-elevation myocardial infarction with a special angiographic pattern in the form of extensive and multi-vessel thrombosis, regardless of atherosclerotic plaques, has posed a new therapeutic challenge. This has been associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
(55 reference statements)
0
19
0
5
Order By: Relevance
“…The reasons for the differential relationships between STEMI and NSTEMI as well as the general trends favoring reductions in these outcomes remain unclear. Indeed, COVID-19 is associated with coronary artery plaque rupture 2 4 and has been implicated as a primary cause of myocardial infarctions in some cases 16 , 17 . It is possible there is some generalized effect related to the pandemic, perhaps related to shelter-in-place orders, that has resulted in an overall reduced propensity to myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the differential relationships between STEMI and NSTEMI as well as the general trends favoring reductions in these outcomes remain unclear. Indeed, COVID-19 is associated with coronary artery plaque rupture 2 4 and has been implicated as a primary cause of myocardial infarctions in some cases 16 , 17 . It is possible there is some generalized effect related to the pandemic, perhaps related to shelter-in-place orders, that has resulted in an overall reduced propensity to myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The United States (US) currently leads the world in disease burden with over 33 million documented COVID-19 cases 1 . Although acute COVID-19 has been associated with a systemic inflammatory cytokine response that can directly contribute to coronary artery plaque rupture, activation of procoagulant factors, and hemodynamic changes that may predispose to ischemia, thrombosis, and therefore myocardial infarction 2 4 , several investigators have paradoxically reported marked declines in the incidence of myocardial infarctions during the COVID-19 pandemic 5 10 . Further bolstering these findings, there have been decreasing cardiac catheterization laboratory activations and percutaneous coronary interventions over the same time period 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Given her positive serology, it is reasonable to assume that at some point before her STEMI, she was infected with COVID-19; however, she was completely asymptomatic. Cardiac injury from COVID-19 is not well understood, however, the majority of cases reported involve patients with a severe form of the disease, usually requiring hospitalization [11][12][13][14][15][16][17]. COVID-19 is associated with hypercoagulability both during acute infection and after recovery 14 [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature review does show the possibility of coronary artery thrombosis secondary to endothelial damage from prolonged severe coronary vasospasm in patients without evidence of atherosclerotic plaque rupture [5][6][7][8][9][10][11]. More recently, coronavirus disease 2019 (COVID-19) has been shown to be associated with various thromboembolic phenomena, however, the majority of cases involving acute coronary artery occlusion have been observed in hospitalized patients with concurrent respiratory failure [12][13][14][15][16][17]. Post-infection coronary artery thrombosis in a recovered asymptomatic patient has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…Through mechanisms that are poorly understood, the virus induces a prothrombotic milieu that leads to the emergence of post infectious microvascular and macrovascular thrombi. [1][2][3][4] Treatment of patients with coincident diagnoses of ACS and COVID-19 is challenging because of uncertain disease pathophysiology. Selection of an appropriate revascularisation strategy depends on the grade of thrombus burden, degree of intracoronary occlusion, preservation of distal flow, duration of thrombus presence, anatomical considerations and clinical status.…”
Section: Introductionmentioning
confidence: 99%